PROYEKSI PENERAPAN SISTEM PEMERINTAHAN ISLAM DI NEGARA REPUBLIK INDONESIA - Jamaluddin Jamaluddin (Al-Bayyinah, 2017)
AbstractThe projection of application sistem Islamic government in Indonesia, have a big chance even seen in social cultural Indonesia nation inspired of yuridis and politic aspects. Likewise, Islam government sistem base on syariah principle that universal can be achieved and applied by all of nation and country.Kata Kunci: Penerapan, Pemerintahan, Islam dan Indonesia.